Double-Negative T Cells Regulate Hepatic Stellate Cell Activation to Promote Liver Fibrosis Progression via NLRP3 - Yang, Yi; Sheng, Yongjia; Wang, Jin; Zhou, Xiaohong; Li, Wenyan; Zhang, Caiqun; Guo, Li; Han, Chenyang (Frontiers in Immunology, 2022)
AIM：We mainly explored the role and mechanism of DNTs in liver fibrosis METHODs：DNTs were co-cultured with mouse hepatic stellate cells (HSCs). Later, cell viability was detected by CCK-8 assay; α-SMA expression was measured through fluorescence staining; TNF-α, IL-6 and MMP-9 levels were measured by ELISA; and the expression of Bcl-2, TGF-β1, NLRP3, ASC and TNFR1 proteins in HSCs was detected by Western-Blot (WB) assay. At the same time, HSC-NLRP3-/- and HSC-TNFR1-/- are used to explore the mechanism. In mouse experiments, mice were intraperitoneally injected with DNTs, afterwards, the hepatic tissue fibrosis degree was detected by Masson staining, α-SMA expression was measured through immunohistochemical (IHC) assay, and histopathological changes were detected by sirius-red staining and H&E staining. RESULTS：The results suggested that DNTs promoted HSC activation and NLRP3 activation. the effect of DNTs on activating HSC-NLRP3-/- was suppressed, and the difference was significant compared with HSCs.HSC-TNFR1-/- activation was also inhibited. To explore the mechanism of DNTs-secreted TNF-α in TNFR1-NLRP3 activation, we transfected DNTs with TNF-α siRNA, as a result, DNTs with TNF-α silencing did not significantly affect HSC activation. DNTs promoted hepatic tissue fibrosis progression and HSC activation, after treatment with NLRP3 inhibitor, the effect of DNTs on promoting fibrosis was suppressed. CONCLUSION：We discovered that DNTs played an important role in liver fibrosis, and that DNTs promoted HSC activation via the TNF-α-TNFR1-NLRP3 signal axis, thus further promoting liver fibrosis progression.